A REVIEW ON COVID-19-A GLOBAL BATTLE BETWEEN LIFE AND DEATH - HANGARGEKAR, CHITRA B.; QUAZI, RUBIYA S.; JOSHI, AMOL A. (International Journal of Current Pharmaceutical Research, 2020)
Currently, the globe is affected by a severe pandemic scenario of COVID-19 infection. The Covid-19 infectious disease is spreading everywhere on the globe particularly in developed countries like China, u. s. Italy, France, Spain, Iran, England, Germany, South Korea, etc. a deadly disease of a unique coronavirus (COVID‐19 or 2019‐CoV) infection has exhibited significant threats to global health, and also the economy. Following an outbreak of pneumonia without a transparent cause within the city of Wuhan in China, a novel strain of coronavirus (2019-nCoV) was detected in December 2019. Coronavirus is called for the spikes that protrude from their membranes just like the sun's corona. In line with WHO, Common signs of infection embrace fever, cold, cough, and respiratory difficulties like dyspnea, pneumonia. Within the absence of treatment for this virus, there's an imperative got to notice various strategies to manage the unfold of disease. It's “Corona time,” however; unfortunately, it's the virus that we tend to speak. In this paper, the origin of the viral infection, the clinical characteristics of Covid-19, etiology, pathogenesis, symptoms treatment and hindrance of Covid-19 are comprehensively detailed. At the time of this writing there are more queries than answers. The aim of our article is to provide a comprehensive understanding of COVID-19 to the peoples, so they'll better understand it and prevent it.